Kompensasi Terhadap Kinerja Guru Pada Sekolah Dasar Negeri Jatiwaringin X Bekasi - Kus Daru Widayati (Universitas Bina Sarana Informatika, 2019)
Compensation is one of the important aspect at the company, because it will increase the employees's motivation during their working time. The employee who get compention will feels like their ability was recognised and appreciated by the company, with the result that makes them more hsrd working. The aim of this research was to identify the effect of compentation toward performance of the teachers at the Sekolah Dasar Negeri Jatiwaringin X Bekasi. This research used description quantitative with questioner instrument 30 respondents. The sampling technique that used was saturated sampling. There are several techniques that used on this research, such as coefficient correlation test, coefficient determination test, and regression, all od the datas were analyzed by SPSS version 21. The result showed a positive effect between compentation and teacher's performance. The bound of compentation and teacher's performance got R= 0,493 as its result, it could be classified as the strong category. While, the effect of compentation toward teacher's performance was KD=0,493 equal with 49,3%, and the regression was Y=15,697 + 0,592x, the b value was 0,592 which is indicated that the increasing 1 point of work compentation will increase 0,592 point of teacher's